2014
DOI: 10.1002/lary.24557
|View full text |Cite
|
Sign up to set email alerts
|

T4a laryngeal cancer survival: Retrospective institutional analysis and systematic review

Abstract: NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 37 publications
1
31
1
1
Order By: Relevance
“…The prognostic relevance of non-surgical (organ-preserving) versus surgical management of advanced-stage LSCC has been discussed extensively since the Veterans Affairs Laryngeal Cancer Study [26]. There is a high level of consensus on the use of TLAR in T4a LSCC, but the clinical diversity and heterogeneity of T3 laryngeal cancers represent a major challenge to established guidelines [17,27]. Based on the idea of organ preservation, TLM and open/endoscopic partial laryngectomies have been proposed as therapeutic alternatives to radiotherapy or chemoradiotherapy in several publications [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic relevance of non-surgical (organ-preserving) versus surgical management of advanced-stage LSCC has been discussed extensively since the Veterans Affairs Laryngeal Cancer Study [26]. There is a high level of consensus on the use of TLAR in T4a LSCC, but the clinical diversity and heterogeneity of T3 laryngeal cancers represent a major challenge to established guidelines [17,27]. Based on the idea of organ preservation, TLM and open/endoscopic partial laryngectomies have been proposed as therapeutic alternatives to radiotherapy or chemoradiotherapy in several publications [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…When facing advanced‐stage laryngeal cancer, treatment decision, in a large number of cases, still faces the choice between total laryngectomy and chemoradiation, which involves a tradeoff: “a diminution in the percentage of survival to preserve the larynx and avoid the burden of total laryngectomy.” This study supplements reports from our institution devoted to the analysis of this tradeoff in specific populations . Besides documenting responses to 2 main questions (“Are you willing to trade a percentage of survival in order to preserve your larynx?” and “What percentage survival would you be willing to lose?”), the present report was intended to search for response‐related variables and to seek for potential differences between otorhinolaryngology patients and laryngeal cancer specialists.…”
Section: Discussionmentioning
confidence: 87%
“…When facing advanced-stage laryngeal cancer, treatment decision, in a large number of cases, still faces the choice between total laryngectomy and chemoradiation, which involves a tradeoff: "a diminution in the percentage of survival to preserve the larynx and avoid the burden of total laryngectomy." [4][5][6][7][8] This study supplements reports from our institution devoted to the analysis of this tradeoff in specific populations. [10][11][12] Besides documenting responses to 2 main questions ("Are you willing to trade a percentage of survival in order to preserve your larynx?"…”
Section: Discussionmentioning
confidence: 98%
“…The results for the T4N0 subgroup were extracted from a previous systematic review that reported survival outcome for all T4a laryngeal cancer [17]. Three articles [18][19][20] were included for the T4N0 subgroup (Table 2) Next, we conducted a systematic review for the studies reporting OS outcome in the T3N+ subgroup.…”
Section: Literature Search Resultsmentioning
confidence: 99%